Environmental characterisation of coffee chaff, a new recycled material for building applications. (30th August 2017) - Ricciardi, P.; Torchia, F.; Belloni, E.; Lascaro, E.; Buratti, C.
Highlights: A new recycled material for building application is proposed: coffee chaff. Different sample thicknesses were produced and tested by means of impedance tube. Porosity and flow resistance were experimentally investigated. LCA was carried out for environmental analysis. Primary embodied energy and greenhouse gas emissions were determined. Abstract: Coffee is one of the most frequently consumed drinks in the world. Coffee chaff, being the dried skin of the coffee bean, the husk, which comes off during the roasting process, is the only by product produced during the coffee beans roasting process. However, methods for the effective utilization of coffee chaff have not been developed. Reuse of coffee chaff, which is the primary residue from the coffee industry, is important for the environment and economy. Recently there have been some attempts to reuse the coffee chaff for energy production, biological materials, and as a nutrient source for solid-state fermentation. The purpose of this work is to propose coffee chaff as sound insulation and absorption material for the building industry. The experimental evaluation of the acoustic absorption properties of new samples made of coffee chaff was carried out. Different sample thicknesses were produced and tested by means of impedance tube, according to ISO 10534-2, showing a good behaviour at middle high frequencies. Porosity and flow resistance were also experimentally investigated. In order to highlight the environmental benefits, Life Cycle Assessment was carried out in terms of primary embodied energy and greenhouse gas emissions, considering a "cradle-to-gate" approach.